Solving Unit Commitment Problem Using Mixed Integer Linear Programming - Singh, Ajay (My University, 2021)
Unit commitment involves the process of preparing a schedule for electrical generator units at every hour interval, subjected to the system and operating constraints. It is a critical problem in power system operations that aims to utilize the operating cost while satisfying all the operating constraints. This thesis work proposes unit commitment algorithms to achieve the target of minimum generation cost. It includes two algorithms based on the Mixed-integer linear programming (MILP) method: UC solution using fmincon and UC solution using MATPOWER. MILP observes a large use in UC operations, as this strategy considers problem functions as continuous and integers. The formulation of deterministic unit commitment has been discussed and the solution is obtained using the mixed integer linear programming method. The success of these fmincon algorithms has been tested on a system containing four generator units while using MATPOWER algorithm tested the three bus system containing three generator units, wind generator, and storage unit.
Keywords: Unit Commitment; Mixed Integer Linear Programming